2009
DOI: 10.1021/jf902342b
|View full text |Cite
|
Sign up to set email alerts
|

Determination and Confirmation of Nicotinic Acid and Its Analogues and Derivates in Pear and Apple Blossoms Using High-Performance Liquid Chromatography−Diode Array−Electrospray Ionization Mass Spectrometry

Abstract: Erwinia amylovora causes fire blight, a serious disease of apple and pear. The bacterial pathogen colonizes the flower stigma and hypanthium, where it multiplies and then invades through natural openings (nectarthodes). E. amylovora requires nicotinic acid as growth factor, and competition for nicotinic acid is being explored as a novel biocontrol strategy. The ability of E. amylovora to substitute nicotinic acid with analogues or derivates as growth factors has not been investigated yet. Furthermore, the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The use of nicotinic acid-degrading strains of Pseudomonas rhizosphaerae and Pseudomonas fluorescens as biocontrol agents to protect plants from the plant pathogen Erwinia amylovora, a nicotinic acid auxotroph, was reported recently (Paternoster et al, 2010). It is unknown whether the tested Pseudomonas strains are chemotactic to nicotinic acid, but it is possible, as the Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of nicotinic acid-degrading strains of Pseudomonas rhizosphaerae and Pseudomonas fluorescens as biocontrol agents to protect plants from the plant pathogen Erwinia amylovora, a nicotinic acid auxotroph, was reported recently (Paternoster et al, 2010). It is unknown whether the tested Pseudomonas strains are chemotactic to nicotinic acid, but it is possible, as the Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Many human, animal and plant pathogens lack pathways for de novo biosynthesis of NAD, and are nicotinic acid or nicotinamide auxotrophs; a few examples include Shigella species, enteroinvasive E. coli strains, Salmonella enterica (serovar Dublin), group A streptococci and Erwinia amylovora (Bergthorsson & Roth, 2005;Paternoster et al, 2010;Prunier et al, 2007;Sorci et al, 2013). The use of nicotinic acid-degrading strains of Pseudomonas rhizosphaerae and Pseudomonas fluorescens as biocontrol agents to protect plants from the plant pathogen Erwinia amylovora, a nicotinic acid auxotroph, was reported recently (Paternoster et al, 2010). It is unknown whether the tested Pseudomonas strains are chemotactic to nicotinic acid, but it is possible, as the Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristic differences between apple and pear in the levels of NicAc were supposed to contribute to the differential susceptibility of these two host species to fire blight (Paternoster et al 2009a). The amount of NicAc on pear hypanthia was positively correlated with the altitude of the growing site and was inversely correlated with the sum of the maximum temperatures in the 30 days before flowering (Paternoster et al 2011).…”
Section: Hypanthium and Nectarymentioning
confidence: 99%
“…Their ability to control fire blight was tested by pear flower assays using P. agglomerans as a carrier for the bacteriophages. Paternoster et al (2009aPaternoster et al ( , 2011 demonstrated that nicotinic acid (NicAc) and/or nicotinamide (NicNH 2 ) are essential for E. amylovora growth, but the amounts of these chemicals on pear and apple flowers do not limit the establishment of the pathogen when competing bacteria are lacking. Degradation of NicAc and consequent inhibition of the pathogen by microbial biocontrol agents have been recently proposed as a new approach for disease control (Paternoster et al 2009a, b).…”
Section: Prevention Of Fire Blight With Chemical Substancesmentioning
confidence: 99%
See 1 more Smart Citation